Late Sodium Current Inhibitors as Potential Antiarrhythmic Agents - Horváth, Balázs; Hézső, Tamás; Kiss, Dénes; Kistamás, Kornél; Magyar, János; Nánási, Péter P.; Bányász, Tamás (Frontiers in Pharmacology, 2020)
Based on recent findings, an increased late sodium current (INa,late) plays an important pathophysiological role in cardiac diseases, including rhythm disorders. The article first describes what is INa,late and how it functions under physiological circumstances. Next, it shows the wide range of cellular mechanisms that can contribute to an increased INa,late in heart diseases, and also discusses how the upregulated INa,late can play a role in the generation of cardiac arrhythmias. The last part of the article is about INa,late inhibiting drugs as potential antiarrhythmic agents, based on experimental and preclinical data as well as in the light of clinical trials.